Macular atrophy development in neovascular age-related macular degeneration during first year of treatment: Incidence and risk factors. Issue 2 (March 2021) - Oliveira, Mariana A; Farinha, Cláudia; Rodrigues, Tiago M; Martins, Amélia; Cachulo, Maria da Luz; Marques, João Pedro; Pires, Isabel; Silva, Rufino
Purpose: To assess the development of macular atrophy, according to the new Classification of Atrophy Meetings criteria, in patients with treatment-naïve neovascular age-related macular degeneration during the first year of treatment with ranibizumab or aflibercept, and to determine baseline factors predictive of atrophy development. Methods: Retrospective subanalysis of three prospective clinical trials that included eyes with treatment-naïve neovascular age-related macular degeneration. Multimodal evaluation was performed with spectral-domain optical coherence tomography, fluorescein angiography, fundus autofluorescence and color fundus photography at baseline and after 12 months of treatment. The main outcome was the macular atrophy type, classified according to Classification of Atrophy Meeting criteria. Logistic regression models were built to test predictors of macular atrophy development. Results: A total of 85 eyes of 85 patients (63% female; mean age: 78.5 ± 6.3 years old) were included. After 12 months of antiangiogenic therapy, all four Classification of Atrophy Meeting types of macular atrophy developed de novo . The atrophy type with highest incidence at end of follow-up was incomplete retinal pigment epithelium and outer retinal atrophy (63.6%; 95% confidence interval: 45.9%–86.0%). A significant association was observed between development at 12 months and the presence of incomplete retinal pigment epithelium and outer retinal atrophy at baseline (odds ratio (95% confidence interval): 22.4 (1.6, 323.5)). The number of injections was predictive of complete outer retinal atrophy development at end of follow-up (odds ratio (95% confidence interval) 1.5 (1.1, 2.1), p = 0.011). Conclusion: Predictors of atrophy development have the potential to change treatment practices. Further research is warranted.